Surface free-energy analysis of energetic poly(glycidyl azide) networks prepared by different reactive systems - Dogan, M; Eroglu, MS; Erbil, HY (JOHN WILEY & SONS INC, 1999)
Change in the surface free energy of poly(glycidyl azide) (PGA) networks prepared with different reactive systems was investigated using the van Oss-Good contact-angle evaluation methodology in order to estimate their wettability properties. The apolar Lifshitz-van der Waals (LW) component of the surface f ree energy of these energetic PGA networks was found to differ only ina minor amount and an average gamma(S)(LW) = 32.2 mJ m(-2) was calculated. The network surface was found to be monopolar and basic (electron donor) in varying degrees in accordance with change of the network bulk structure, mainly due to the presence of oxygen atoms in the PGA chain. The set of the network containing only PG;A and Desmodur N-100 components showed the highest gamma(S)(-) values compared to the other two sets. The main gamma(S)(-) contribution was found to come hom the PGA polymer. A slight decrease of the gamma(S)(-) component was seen when the Desmodur N-100 component was substituted with hexamethylene diisocyanate (HMDI); however a large decrease was seen when Desmodur N-100 was substituted with the isophorone diisocyanate (IPDI) component. This large reduction in the surface basicity of the network was due to increase of the apolar IPDI groups at the surface having low surface tension and also due to decrease of the oxygen atoms belonging to the main chain of PGA at the surface, which resulted in the minimization of the network's basic surface free-energy component. (C) 1999 John Wiley & Sons, Inc.
Keywords: poly(glycidyl azide) (PGA); glycidyl azide polymer (GAP); surface free energy; network; AROMATIC-HYDROCARBONS; COPOLYMERS; SOLUBILITY; POLYMERS; ADHESION; WATER; WORK; Polymer Science